2013
DOI: 10.1002/jso.23396
|View full text |Cite
|
Sign up to set email alerts
|

Chest X‐ray screening for lung cancer: Overdiagnosis, endpoints, and randomized population trials

Abstract: Publication of the National Lung Screening Trial (NLST) generated excitement by concluding that CT screening reduces lung cancer mortality when compared to chest X-ray (CXR) screening. In contrast, CXR screening has long been considered to be ineffective. This is because randomized population trials (RPTs) have failed to demonstrate significant mortality reductions in populations randomized to CXR screening. While these studies demonstrate that CXR screening is associated with significant survival advantages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Earlier lung cancer screening strategies were tested on randomized population trials using annual chest radiography and sputum samples versus no screening. These studies were interpreted as having failed to demonstrate effectiveness (eg, no mortality reduction) in the screened arm, although excess lung cancers were detected, because these were attributed to overdiagnosis (35), which was estimated as $25% of chest x-ray-detected cancers (36). Patz el al.…”
Section: Harms: Overdiagnosis and Overtreatmentmentioning
confidence: 99%
“…Earlier lung cancer screening strategies were tested on randomized population trials using annual chest radiography and sputum samples versus no screening. These studies were interpreted as having failed to demonstrate effectiveness (eg, no mortality reduction) in the screened arm, although excess lung cancers were detected, because these were attributed to overdiagnosis (35), which was estimated as $25% of chest x-ray-detected cancers (36). Patz el al.…”
Section: Harms: Overdiagnosis and Overtreatmentmentioning
confidence: 99%
“…One of the major reasons for this poor prognosis is the lack of effective lung cancer screening or early diagnostic methods . Several studies have evaluated lung cancer screening methods such as X‐ray, sputum cytology, and chest computed tomography (CT); however, such methods yield low sensitivity or specificity and thus are not adequate to diagnose NSCLC at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…As randomized controlled trials (RCT) have shown no reduction in lung cancer mortality compared to control groups it has been concluded by most investigators that screening with chest radiography is ineffective [1] . This view has been repeatedly challenged: most RCT have shown a survival advantage for screened individuals because of a stage shift in diagnosed cancers [4,5] . Because RCT are prone to selection bias (selection of highly motivated individuals and problem of generating two comparable groups) population based cohort studies may give a more realistic view of the situation in medical care [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…This view has been repeatedly challenged: most RCT have shown a survival advantage for screened individuals because of a stage shift in diagnosed cancers [4,5] . Because RCT are prone to selection bias (selection of highly motivated individuals and problem of generating two comparable groups) population based cohort studies may give a more realistic view of the situation in medical care [5,6] . Recently, a group of Italian investigators presented their follow-up data of a large population based cohort study [7] .…”
Section: Introductionmentioning
confidence: 99%